Florpyrauxifen-Benzyl Selectivity to Rice - Velásquez, Juan Camilo; Das Cas Bundt, Angela; Rabaioli Camargo, Edinalvo; Andres, André; Ebeling Viana, Vivian; Hoyos, Verónica (MDPI, 2021)
Florpyrauxifen-benzyl (FPB) is a new class of auxinic herbicide developed for selective weed control in rice. This study aimed to evaluate the effect of environmental conditions, P450 inhibitors, rice cultivar response, and gene expression on FPB selectivity in rice. Field experiments established in a randomized block design showed that rice plant injury due to two FPB rates (30 and 60 g ai ha−1) was affected by planting time and rice stage at herbicide application. The injury was higher at the earliest planting season and more in younger plants (V2) than larger (V6 and R0). However, no yield reduction was detected. Under greenhouse conditions, two dose-response experiments in a randomized block design showed that spraying malathion (1 kg ha−1) before FPB application did not reduce herbicide selectivity. The addition of two P450 inhibitors (dietholate and piperonyl butoxide, 10 g a.i. seed-kg−1 and 4.2 kg ai ha−1, respectively) decreased the doses to cause 50% of plant injury (ED50) and growth reduction (GR50). However, it seems not to compromise crop selectivity. Pampeira cultivar showed lower ED50 and GR50 than IRGA 424 RI. A growth chamber experiment was conducted in a completely randomized design to evaluate the gene expression of rice plants sprayed with FPB (30 and 60 g ai ha−1). Results showed downregulation of OsWAKL21.2, an esterase probably related to bio-activation of FPB-ester. However, no effect was detected on CYP71A21 monooxygenase and OsGSTL transferase, enzymes probably related to FPB degradation. Further research should focus on understanding FBP bio-activation as the selective mechanism.